Erythema Multiforme and its Clinicopathological Features in a Horse in Brazil - Braga, Pollyana Rennó Campos; Conceição, Lissandro Gonçalves; Loures, Fabricia Hallack; Basso, Roberta Martins; Filho, José Paes de Oliveira; Borges, Alexandre Secorun (Acta Scientiae Veterinariae, 2021)
Background: Erythema multiforme (EM) is an immune-mediated skin disease which may manifest as cutaneous or mucocutaneous lesions. It is uncommon in horses. EM lesions have a symmetrical bilateral distribution; they are usually urticarial, necrotizing, and, less commonly, ulcerative. In equines, the trigger is usually unknown, and cases are often classified as idiopathic. Diagnosis is based on a thorough history and physical and histopathological examination of lesions. According to the clinical presentation and histopathological characteristics of the cutaneous lesions, this case is the first report to describe diagnosis and treatment of a horse with EM in Brazil. Case: A Quarter Horse filly was followed clinically for 12 months after sudden onset of skin lesions at 18 months of age. The initial lesions were non-alopecic papules with a symmetrical bilateral distribution. Six months after onset, the skin lesions maintained the original distribution pattern; however, they had progressed to papules and plaques with varying annular, arciform, serpiginous, targetoid, or alopecic appearance. At 8 months, the same distribution pattern and appearance remained, but the lesions had become more severe and extensive, with involvement of the labial commissures and perineal region, without any erosions/ulcerations, scaling/crusting, pain, or pruritus. At 12 months, new nodular lesions were found on the medial and lateral surfaces of the hind limbs, neck, bilateral trunk, and root of the tail. The lesions were firm, non-pruritic, and non-tender on palpation. Swabs were obtained from the papular lesions. Skin specimens were also obtained with a 6-mm punch and via incisional biopsy and histological sections were made. Bacterial and fungal cultures were negative. Appropriate stains did not identify fungal structures, were negative for acid-fast bacilli, and did not reveal any metachromatic granules in the sampled cell population. The histopathological findings were characteristic of immune-mediated disease, with a vacuolar interface dermatitis affecting the hair follicles more than the epidermis, necrotic keratinocytes, lymphocyte satellitosis, leukocytoclastic mixed vasculitis of the mid-dermis and deep dermis, and variable granulation tissue, consistent with erythema multiforme and leukocytoclastic vasculitis. Immunosuppressive therapy with corticosteroids and oral supplementation with omega-3 and omega-6 fatty acids and vitamin E were prescribed. After institution of therapy, no new lesions developed, the existing lesions remained stable (though permanent), and hair regrew in the previously alopecic areas. All physiological parameters remained normal throughout the follow-up period. Discussion: Erythema multiforme is rarely reported in horses. According to our literature review, this is the first description of EM in horses in Brazil. EM should be included in the differential diagnosis of horses that present with plaques in a diverse, geographic distribution and a negative initial dermatological screening examination. Further clinical investigation is warranted, with special attention to potential antigenic triggers. A thorough drug and dietary history and close attention to comorbidities are essential, as the suppression of potential culprit factors has important prognostic value and contributes to the elucidation of EM triggers.